Who Suffers Most From Being Involved in Bullying—Bully, Victim, or Bully‐Victim?. (2nd January 2019) - Mark, Lauraliisa; Värnik, Airi; Sisask, Merike
ABSTRACT: BACKGROUND: Bullying has been associated with many mental health problems. The effect of bullying has been found to be affected by the way students are involved in bullying. The purpose of the study was to explore the association between mental well‐being, hopelessness, and being involved in bullying (as a bully, victim, or bully‐victim), and to detect more harmful bullying types to students' mental well‐being. METHODS: The study was conducted among Estonian students from grades 5 to 9 (N = 2048). The survey was nationwide, cross‐sectional, anonymous, and web‐based by nature. Mental well‐being was assessed by using WHO‐5 well‐being index and hopelessness by 1‐item Beck Hopelessness Scale. RESULTS: The odds for being severely distressed (ie, students expressing both poor mental well‐being and hopelessness) were greater for both sexes bullying others and being victims of bullying. For bully‐victims the odds were greater for girls only. The victims of extensive cyber bullying expressed the lowest level of mental well‐being for both sexes. CONCLUSIONS: Boys might be the most vulnerable if being pure victims, while girls if being bully‐victims. More attention should be paid to cyber bullying, as victims of extensive cyber bullying had the lowest level of mental well‐being.